2015
DOI: 10.33607/bjshs.v3i98.88
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Standing Long Jump Technique Performed by Subjects From Different Age Groups

Abstract: Background. The aim of this study was to determine kinematic parameters relevant for the proficient performance of standing long jump (SLJ) test in boys and adolescents. Methods. The investigation was conducted on 120 participants divided into five experimental groups of 20 boys and adolescents aged 4–18 and one control group composed of 20 students from the second year of Faculty of Kinesiology whose performance was considered as a model of proficient execution of analysed test. The set of variables was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 23 publications
2
16
0
Order By: Relevance
“…Indeed, the information obtained from the IMU method could provide accurate explanations about the differences among children' developmental levels. It is interesting that no parameters were statistically different for each of the level comparisons, suggesting that the IMU also reflects the complexity of identifying reliable differences among 8-to 10-year-old participants (Hraski et al, 2015;Nikolic´et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Indeed, the information obtained from the IMU method could provide accurate explanations about the differences among children' developmental levels. It is interesting that no parameters were statistically different for each of the level comparisons, suggesting that the IMU also reflects the complexity of identifying reliable differences among 8-to 10-year-old participants (Hraski et al, 2015;Nikolic´et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…All participants were attending two physical education lessons per week and were familiar with the SLJ. The age range of the participants was selected to span stages of varying SLJ proficiency level in the course toward mastery (Gabbard, 2011) even though motor coordination and technical performance required for SLJ skill are not yet stable and recognizable this early (Hraski et al, 2015). Hence, the current age range was deemed adequate for sampling participants that might exhibit differences in their rate of development.…”
Section: Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…[Huelke 1998]. Several studies have been conducted that study the differences between the child and adults behavior and motion, in terms of mass body, motor control, skillful, coordination, and energy [Aloba 2019;Hraski et al 2015;Huelke 1998;Nader et al 2008]. More particularly, Jain et al [2016] found that naive viewers can identify if a motion was performed by a child or an adult, even when they are completing the same actions.…”
Section: Related Workmentioning
confidence: 99%